Band-like transport in high mobility unencapsulated single-layer MoS2 transistors - Jariwala, Deep; Sangwan, Vinod K.; Late, Dattatray J.; Johns, James E.; Dravid, Vinayak P.; Marks, Tobin J.; Lauhon, Lincoln J.; Hersam, Mark C. (Applied Physics Letters, 2013)
Ultra-thin MoS2 has recently emerged as a promising two-dimensional semiconductor for electronic and optoelectronic applications. Here, we report high mobility (>60 cm(2)/Vs at room temperature) field-effect transistors that employ unencapsulated single-layer MoS2 on oxidized Si wafers with a low level of extrinsic contamination. While charge transport in the sub-threshold regime is consistent with a variable range hopping model, monotonically decreasing field-effect mobility with increasing temperature suggests band-like transport in the linear regime. At temperatures below 100 K, temperature-independent mobility is limited by Coulomb scattering, whereas, at temperatures above 100 K, phonon-limited mobility decreases as a power law with increasing temperature. (C) 2013 AIP Publishing LLC.

Black phosphorous nanosheets: prospective field emitter - Late, Dattatray J.; Erande, Manisha B.; Suryawanshi, Sachin R.; More, Mahendra A. (2015 28th International Vacuum Nanoelectronics Conference (IVNC), 2015)
We report for the first time field electron emission investigations on few layered black phosphorous nanosheets emitter's synthesized using chemical method with thickness similar to 2-5 nm. The turn-on electric field required to draw an emission current density of similar to 10 mu A/cm(2) was found to be similar to 4.2 V/mu m. Furthermore, a few layer black phosphorous nanosheets emitter deliver an large emission current density of similar to 170 mu A/cm(2) at an applied field of similar to 7.5 V/mu m. The emission current versus time plot measured at the preset current values of similar to 5 mu A shows field emission current fluctuations within +/- 10% of the average value indicating the well stable nature of black phosphorous field emitter. Thus, the two dimensional black phosphorous nanosheets synthesized using simple electrochemical exfoliation method can be realized and utilized for the next generation micro/nanoelectronics and flat panel field emission based display applications.

Bessel's polynomial fitting for electrospun polyacrylonitrile/polyaniline blend nanofibers based ammonia sensor - Anwane, Rajashree S.; Kondawar, Subhash B.; Late, Dattatray J. (Materials Letters, 2018)
In the present paper, we report the fabrication of electrospun polyacrylonitrile/polyaniline (PAN/PANI) blend nanofibers by electrospinning and polymerization and Bessel's polynomial model applied for its ammonia sensing characteristics. As-fabricated PAN/PANI blend nanofibers were characterized by scanning electron microscopy and Fourier transform infrared spectroscopy for the confirmation of fibers with nanoscale and blends of PAN and PANI. The semiconducting behavior of the PAN/PANI blend nanofibers was found to respond quickly towards ammonia gas. Sensitivity of the blend was obtained at near room temperature for different concentrations of ammonia. Bessel's polynomial function was found to be well fitted with the experimental data for the response towards ammonia gas. (C) 2018 Elsevier B.V. All rights reserved.